Peradaban Islam di Nusantara Era Walisongo dan Karakteristik Budayanya - Lailatur Rizqi Milatur Rakhmah; Robiatul Adawiyah; Naila Izza Nur Salimah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Until now, there are still many cultural forms that are at issue because they are not the original innate nature of Islam in Arabia. Likewise, the Indonesian people, where most of the community opposes Islamicstyle culture because there is no naqli argument, but others want to state and admit that culture is a feature of Islam in Indonesia. So in this study, it will be explained about the study ofintegration in this archipelago which began in the Walisongo era and has existed until now. The method used in this study is library research where researchers will conduct a study into various literatures related to Islam and Culture in the archipelago from various documents. The results found are Islam in Java, Javanese society still maintains tahlilan, slametan and culture attached to the community whose values have changed from what was originally a Hindu-Buddhist pattern to Islam, besidesthe pesantren education system also colors this integration, Islam in Sumatra is supported by three forces, namely pesantren, markets and palaces, and Islam in eastern Indonesia carried out by walisngo students on the island of Java.Through this research, it will be found both theoretically and practically what happened regarding the integration of Islam and Nusantara culture.